Influencia de un programa de juegos pre deportivos del tenis, sobre la coordinación viso manual, en niños de 6 a 8 años de la institución educativa la Adiela (2015)
The development of children, is led primarily by the environment in which it unfolds, will be your home, which provide the first tools and notions for your development appropriate, also their interaction with the community where the child lives will provide tools to improve their psychomotor development through play with other children in the community will be key to improving motor development. Now, the school becomes a second home in fostering the development of children, not only in the cognitive if not in the psychomotor driving. Teachers being responsible in working these capabilities in their daily work, not just the physical education teacher interact so that the mobility of the boy is enhanced. From this problem it arose this question What is the influence of a program of pre tennis sports games on the hand eye coordination in children 6-8 years of educational institution Adiela? The research is a quantitative research, longitudinal type, with a descriptive range is characterized by a quasi-experimental research. Which consisted of work plans for 36 class sessions with children 6 to 8 years of School TheAdiela, for which two groups of 12 children, where pre test and post test were applied during the used Viso coordination work based on manual. Based on the overall goal, it was determined that if there was influence of the program of games and pre sporting tennis exercises coordination semblance manual children 6-8 years of Educational Institution The Adiela, which showed significant progress with respect to can demonstrate control group also showed progress according to its own motor development. I starting from the hypothesis 1 was evident that the exercises and games pre sports of tennis, influenced the strengthening of coordination manual semblance children 6-8 years of Educational Institution The Adiela. Furthermore tennis is the most successful for improving psychomotor development and coordination specifically semblance manual children 6 to 8 years sport.